MASS TRANSFER INVACUUM OSMOTIC DEHYDRATION OF ANANAS COMOSUS L. MERR "PINEAPPLE" S LICES - Dávila Solar, Luis (2005)
The temperature and pressure effects on the mass transfer kinetics during vacuum osmotic treatment in pineapple slices were analized. Experiments were carried out with solution of sucrose of 65 oBrix at temperatures of 40 and 50oC, pressure of 1 013, 220 and 100 mb, for 30, 60, 120, 180 and 240 min. The highest mass transference was obtained at 100 mb under the specified working conditions.